Doping of silicon nanocrystals. (May 2017) - Arduca, Elisa; Perego, Michele
Abstract: Over the last decades silicon nanocrystals (Si NCs) were the subject of an intense research activity, due to their optical and electronic properties. Different experimental approaches were developed to synthesize Si NCs embedded in a dielectric matrix as well as freestanding Si NCs with well-controlled structural and morphological characteristics. Actually, as in the case of bulk semiconductors, the fine tuning of their optical and electronic properties is related to the effective capability to control doping, i.e. incorporation impurity atoms within these nanostructures. Even if Si NCs incorporating both p-type and n-type dopants were successfully synthetized, several fundamental issues need to be understood. First of all, from a structural point of view, it is very hard to obtain information about dopant location with respect to Si NCs surface and core. This uncertainty is related either to the intrinsic limitations of the experimental approaches for the synthesis and for the analysis of doped Si NCs, or to the difficulties in the modeling of these nanostructures. Moreover, from a fundamental point of view, it is not clear if impurity incorporation in Si NCs effectively results in the generation of free charge carriers as in the case of bulk silicon. This review presents an overview of the recent progress in the field, focusing on the latest results related to doping of Si NCs. In particular the problem of thermodynamic stability of impurities into Si NCs and the problem of modulation of electrical properties of Si NCs will be systematically addressed.